'Killing off' the (unbearable) sex worker: prostitution law reform in Ireland. Issue 3 (2nd September 2019) - Ward, Eilís
ABSTRACT: This article draws on the work of Jessica Benjamin and of Sarah Ahmed to argue that the adoption of a Sex Purchase Ban (SPB) by the Irish state constituted a form of affective governmentality that was derived from a deep psychic discomfort towards the presence of 'errant' female sexuality. The ban, enshrined in the Criminal Law (Sexual Offences) Act 2017, followed a long campaign by radical feminist activists but also saw, for the first time in Irish history, pro-sex work activism in the form of sex worker organisation.